Application of a graded approach in regulating nuclear installations. (IAEA-TECDOC, 2021)
"This publication addresses the basics of the application of a graded approach in the regulatory oversight of nuclear installations, describes the approaches currently implemented by several regulatory bodies around the world and, based on these examples, proposes a generic methodology for application of a graded approach to regulation of nuclear installations. The publication provides practical examples and information on developing and implementing strategies and processes for all regulatory functions."--Publisher's description.